Shariah-compliant hotel in the Middle East, Singapore and Malaysia: practice and problem - Mahamod, Lukman Hakim; Wan Shamsuddin, Wan Norshafiqah; Othman, Rashidi; Hashim, Khairusy Syakirin Has-Yun; Wan Yahya, Wan Nur Amirah; Mohd Hatta, Farah Ayuni (Yamani Angle Sdn Bhd, 2021)
The increasing number of Muslim population has given a direct impact of the increasing number of Muslim travellers and the demand for Islamic tourism. Besides halal food and prayer place, other facilities have gone through the innovation to meet this demand. One of the facilities is an accommodation known as Shariah-Compliant Hotel (SCH) or Islamic Hotel or Muslim-friendly hotel. Various terms are used but the concept and practice are in compliance with Shariah. Middle East countries are the pioneer of this new hotel concept as they abide by the Shariah law practice. The concept has spread and applied by many countries around the world including Singapore and Malaysia. This paper is a part of research on Muslim-friendly compliant Tourism Accommodation Premises (TAP) in improving the Muslim Friendly Hospitality Services (MFHS) Malaysian Standard. The aim of the research is to identify the issues arise from the implementation of SCH based on these three different countries which are the Middle East, Singapore and Malaysia.